Derivation of the nuclear level density distribution and the partition function - Syros, C.; Livadas, E. (HNPS Advances in Nuclear Physics, 2019)
The nuclear density matrix and the partition function have been derived, from Generalized Random. Quantum Field Theory. The nuclear level density distribution has been deduced as a function of the energy level density. The temperature follows as a functional of the nuclear interaction Hamiltonian.